Leiomioma benigno metastisante – um caso clínico patológico - Ducla-Soares, J. L. (2002)
The case of a post-menopausal woman with vaginal bleeding and bilateral asymptomatic lung nodules is discussed. Radiologic patterns of lung nodules are extensively analysed and possible aetiologies are discussed. The final pathologic diagnosis was benignmetastasizing leiomyoma.